2021
DOI: 10.1111/jgh.15391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of esophageal motility disorders in patients with laryngopharyngeal reflux symptoms

Abstract: Background and Aim: Esophageal motor dysfunction may underlie impaired bolus/refluxate clearance in laryngopharyngeal reflux (LPR). However, the prevalence of esophageal dysmotility and its correlation with reflux parameters and symptoms in LPR is not well established. The aim of this study was to evaluate the prevalence of coexisting esophageal dysmotility among patients with suspected LPR. Methods: This was a retrospective cohort study of 194 consecutive patients with LPR symptoms referred for high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Even then, I'd make it clear to patient the small amount of evidence available WC: Esophageal dysmotility may be associated with LPR symptoms (?secondary to reflux versus worsens reflux versus no causative relations). Our study of patients with LPR symptoms and HRM found that abnormal findings are common (43%), including 13.4% with EGJOO or a major peristaltic disorder [11]. Impaired esophageal motility may also correlate with worse LPR symptoms.…”
Section: Introductionmentioning
confidence: 64%
“…Even then, I'd make it clear to patient the small amount of evidence available WC: Esophageal dysmotility may be associated with LPR symptoms (?secondary to reflux versus worsens reflux versus no causative relations). Our study of patients with LPR symptoms and HRM found that abnormal findings are common (43%), including 13.4% with EGJOO or a major peristaltic disorder [11]. Impaired esophageal motility may also correlate with worse LPR symptoms.…”
Section: Introductionmentioning
confidence: 64%
“…However, the prevalence of IEM per CCv3.0 in our study is lower than reported in previous literature. Sikavi et al 14 reported a prevalence of IEM of 30.0%, though this was in a population previously diagnosed with laryngopharyngeal reflux. Boland et al 2 also reported a prevalence of 31.0%, a number that had increased with the advent of HRIM.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, Sikavi et al observed that LPR patients (with or without coexisting motility disorder) had reduced proximal esophageal contractibility at the high-resolution manometry, which significantly predicted increased of HREs [ 2 ]. The same team reported in another publication that 43.3% of patients with LPR at the HEMII-pH had abnormal findings at the high-resolution manometry, with the ineffective esophageal motility being the most common diagnosis [ 54 ]. Interestingly, recent findings reported that most HREs are weakly or nonacid [ 6 , 38 , 41 , 55 ], which supports the consideration of alginate or magaldrate in the therapeutic strategy [ 32 , 55 ].…”
Section: Diagnosis Of Reflux and Place Of Ph Studymentioning
confidence: 99%